A(n) = a₁.(r)ⁿ⁻¹, where a₁ = 1st term, r= common ratio and n, the rank
In the formula given a₁ = 5, r = 3/2 and n = 6 (we have to find the 6th term value).
a₆ = 5.(3/2)⁶⁻¹ = 5.(3/2)⁵ = 1215/32 (answer C)
Answer:
is A
Step-by-step explanation:
Answer:
x = 4/15 and x= 10/3
Step-by-step explanation:
|9x-7|=|6x+3|
There are two solutions, one positive and one negative.
(9x-7)=6x+3 - (9x-7)=6x+3
We will take the positive one first
(9x-7)=6x+3
Subtract 6x from each side
(9x-6x-7)=6x-6x+3
3x -7=3
Add 7 to each side
3x-7+7 = 3+7
3x = 10
Divide by 3x/3 = 10/3
x = 10/3
Now we will take the negative solution
- (9x-7)=6x+3
Distribute the negative sign
-9x+7 = 6x+3
Add 9x to each side
-9x+9x+7 = 6x+9x+3
7 = 15x+3
Subtract 3 from each side
7-3 = 15x +3-3
4 = 15x
Divide by 15 on each side
4/15 =15x/15
4/15 =x
Answer:
26.42139285
Step-by-step explanation:
26x26 + 4.7x4.7 = c2
676 + 22.9 =c2
698.09=c2
square root of 698.09=26.42139285
26.42139285 = c
Answer:
x = 5
Step-by-step explanation:
x^2/(x + 5) = 25/(x+5) Subtract the right side from both sides.
x^2/(x + 5) - 25/(x + 5) = 0
x^2 - 25
======= = 0
x + 5
(x + 5)(x - 5)
============= = 0
(x + 5)
Cancel x + 5 in the numerator and denominator.
x - 5 = 0
x = + 5
Does it check?
x^2/(x + 5) = 25/(x + 5)
x = 5
5^2/(10) = 25/10
25/10 = 25/10 Yes it checks.